(untitled) (Indonesian Journal of Agrarian Law, 2026)
This study examines the role of the Central Java Provincial Public Housing and Settlement Area Office (Disperakim) in the preparation stage for land acquisition for the construction of the Bawen–Yogyakarta Toll Road in Semarang Regency, as well as its legal impact on the rights of affected communities. Using an empirical juridical approach with a descriptive qualitative method that compares das sein and das sollen through interviews, document studies, and field observations. The results of the study show that the Disperakim is positioned as the secretary of the Preparation Team based on Law No. 2 of 2012 and Government Regulation No. 19 of 2021 jo. PP No. 39 of 2023, with strategic functions including notification of development plans, initial data collection, facilitation of public consultations, as well as preparation of location determination and location concept documents to the Governor. In the field, the Disperakim faced the challenge of the gap in public understanding and differences in land ownership status, but no formal objections or legal disputes were found. The public’s right to information, participation, and procedurally appropriate compensation has been fulfilled. This study concludes that the role of the Disperakim is integrative-coordinating as the main facilitator who ensures procedural order and legality of the land acquisition process, not through an exclusive task that stands alone.